Історико-хронологічний довідник "Памʼятні дати в історії України," як наукове джерело у вивченні історіографії, історії і культури України - Палієнко, В. (Історіографічні дослідження в Україні, 1998)
The author tells history of the creation of the edition, shows its concept structure and on concrete examples demonstrates the ways of using it in scientific studies.